Countering “Arctification”: Dawson City’s “Sourtoe Cocktail” - Elizabeth Ann Cooper; Michelle Spinei; Alix Varnajot (Journal of Tourism Futures, 2020)
Purpose - The purpose of this paper is to focus on the Sourtoe Cocktail, a custom in Dawson City, Canada’s Yukon, in which participants drink a shot of alcohol with a dehydrated human toe in it. Springing from a local legend, the thrill-inducing Sourtoe Cocktail has attracted the attention of tourists. The paper reveals insights from this particular case study in order to discuss potential future tourism trends within the Arctic, especially in regard to the development of a sustainable tourism industry. Additionally, it illustrates how local communities can avoid negative effects of “Arctification.” Design/methodology/approach - The case study is deconstructed through Dean MacCannell’s (1976) framework of sight sacralization. The Sourtoe Cocktail is analyzed based on the five stages of the framework, which helps to reveal the various elements at play at the local level. The framework specifically highlights linkages between society and the Sourtoe Cocktail as a product in order to understand how it became a tourist attraction. Findings - The use of MacCannell’s sight sacralization framework reveals the intricate relationship of the Sourtoe Cocktail to both the Arctic and the local folklore of the Klondike Gold Rush. In addition, it is argued that the activity can serve as an example of avoiding “Arctification” processes for northern communities. Originality/value - The originality of the study lies in the application of the sight sacralization framework to an ordinary object – a toe – instead of an object of inherent historical, aesthetic or cultural value. The paper proposes a complementary study to the recommendations provided in the Arctic Tourism in Times of Change: Seasonality report (2019) for the development of sustainable Arctic societies.